Pengaruh Model Cooperative Tipe Picture And Picture Terhadap Keterampilan Menulis Permulaan Pada Peserta Didik Kelas II Sd Negeri 6 Parittiga - Putri Yani; Nurjanah; Silvio Juliana Nabela (Universitas Muhammadiyah Bangka Belitung, 2024)
This research was motivated by several problems, namely the lack of students’ writing skills in beginning writing and distinguishing one letter from another, resulting in repeated errors, and the lack of use of varied methods in learning. This research aims to determine the effect of the picture and picture-type cooperative model on initial writing skills in class II students at SD 6 Parittiga. This type of research uses a quantitative approach with the pre-experimental design method and a one-group pretest-posttest design. The sampling technique used is saturated sampling. The study sample consisted of 25 second-grade students at SD 6 Parittiga. The data collection technique used was testing. The data analysis technique used was a normality test, a hypothesis test (t-test), and a paired-sample t-test. Based on the research results, the data in the normality test using Shapiro Wilk obtained pretest data of 0.102 and posttest data of 0.088, which is greater than 0.05, so the data can be interpreted as having a normal distribution. In hypothesis testing, the average pretest and posttest scores were 65.20 and 88.00. Hypothesis testing is obtained from the paired sample test with a value of 0.000 < 0.05. Thus, it can be concluded that Ha has an influence and H0 has no influence, meaning that there is an influence of the picture and picture type cooperative model on initial writing skills in class II students at SD Negeri 6 Parittiga.